2011 International Conference of Soft Computing and Pattern Recognition (SoCPaR) 2011
DOI: 10.1109/socpar.2011.6089123
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid algorithm for segmentation of MRI images based on edge detection

Abstract: the main disadvantage of traditional global thresholding techniques is that they do not have an ability to exploit information of the characteristics of target images that they threshold. In this paper, we propose a new approach based on combination of modified p-tile and edge detection algorithms to have more accurate object segmentation. Using our proposed method, it is shown that almost all of our experiments on MRI images resulted to better object segmentation than using traditional methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…This process detects boundaries between objects and the background in the image at which the image brightness changes sharply or more formally has discontinuities [4]. The image containing these boundaries is known as edge map.…”
Section: Edge Detection Methodsmentioning
confidence: 99%
“…This process detects boundaries between objects and the background in the image at which the image brightness changes sharply or more formally has discontinuities [4]. The image containing these boundaries is known as edge map.…”
Section: Edge Detection Methodsmentioning
confidence: 99%
“…Different approaches, used to segment the MR images, are reported in the literature. 19,20,22,23,31,35 It is observed that the captured MR images suffer from different limitations like broken boundaries, presence of noise, imprecise or incomplete lines, curvatures etc. which demand some form of pre-processing operations and denoising before segmentation technique is applied.…”
Section: Literature Review On the Existing Work And Limitationsmentioning
confidence: 99%
“…In Ref. 35, a modified method of MR image segmentation is proposed where the combination of p-tile and edge detection is used. In Ref.…”
Section: Literature Review On the Existing Work And Limitationsmentioning
confidence: 99%
“…Thresholding is one of the easiest and most frequently used techniques to segment MRI data by separating the foreground from background of image [12,13]. Thresholding approach can further be classified as global thresholding and local (adaptive) thresholding.…”
Section: Thresholdingmentioning
confidence: 99%
“…Due to simplicity and easy implementation of global thresholding, this method is more popular. P-tile method is one of the earliest thresholding methods based on the gray level histogram [12,14]. Here P refers to the word "percentile".…”
Section: Thresholdingmentioning
confidence: 99%